Physiological impact of Trichoderma viride agents on the quality and production of melon that is grown on soils continuously cropped to melon - Jingyi Liu; Hua Lian; Jingwei Dou; Jingjing Li; Guangliang Zhu; Jiatong Wang; Guangshu Ma; Mei Li (Frontiers in Sustainable Food Systems)
The issue of ongoing cropping barriers is getting worse as China’s melon planting area steadily grows, and the melon industry’s sustainable growth is being negatively impacted by the steadily diminishing yield and quality of the fruit. Trichoderma is a probiotic that can enhance the physiological traits of crops, encourage their growth, and raise their yield and quality. It is yet unknown, though, how Trichoderma influences the growth, physiological traits, and yield of melon grown on soils continuously cropped to melon. Trichoderma viride kf57 agents at 1.0 × 104, 8.0 × 104, 6.4 × 105, and 5.12 × 106 CFU/g and no Trichoderma viride agents (CK) were utilized as treatments. At the seedling and fruiting stages, a pot experiment and a bedding experiment were conducted to study the physiological properties and yield of melon under varying concentration of Trichoderma viride kf57 agents. As a result of the application of T. viride agents, the indexes of melon seedlings were all significantly improved. The treatment of 6.4 × 105 CFU/g had the best promoting effect on the morphology of melon seedlings, and the plant height, stem diameter, leaf area, fresh weight of whole plant, dry weight of whole plant, root shoot ratio, and strong seedling index of melon seedlings increased by 90.39, 46.30, 37.55, 81.35, 100.62, 51.47, and 240.00%, respectively, compared with CK. The results showed that different amounts of T. viride agents could improve physiological and biochemical indices of melon leaves during the fruiting stage; the treatment of 6.4 × 105 CFU/g was the most effective; chlorophyll content, nitrate nitrogen content, sucrose content, reducing sugar content, free proline content, nitrate reductase (NR) activity, peroxidase (POD) activity, and superoxide dismutase (SOD) activity of melon leaves increased at 30 days after melon pollination. Melon quality and yield was also enhanced by the use of T. viride agents, with the treatment of 6.4 × 105 CFU/g T. viride agents having the best boosting effects. The melon fruit’s transverse diameter, vertical diameter, single fruit weight, and yield all increased. The amount of soluble solids, vitamin C, soluble protein, soluble sugar, and sugar acid ratio also increased. In conclusion, by promoting the morphology of melon grown on soils continuously cropped to melon seedlings, T. viride agents can improve the physiological characteristics of melon grown on soils continuously cropped to melon and improve the production and quality qualities of melon. When using T. viride kf57 agents, 6.4 × 105 CFU/g is the highest effective dosage. The study revealed that T. viride agents had significant potential as biological agents as they showed good results in melon yield and quality formation, as well as in enhancing seedling quality.